THE TRANSLATION OF SLANG WORDS IN TO ALL THE BOYS I’VE LOVED BEFORE MOVIE - Annisah Inriani Harahap; Syahron Lubis (ELP (Journal of English Language Pedagogy), 2021)
The objectives of the study to find out the types of English slang words used and strategies in translating slang words from English to Bahasa uttered in “To All the Boys I’ve Loved Before” movie. The data were collected using the theory of Partridge and Bloomfield, and theories of translation strategies by Mona Baker. The result showed that there were 61 slang words were found in this movie. They were classified into 7 types of slang words namely cockney slang, public house slang, workmen’s slang, slang in theater, slang in art, slang in public school and university, and society slang. Society slang is the utmost type of slang used in the movie and other pop cultures. The translation strategies used were translation by more general word, translation by more neutral/ less expressive, translation by paraphrase using the related word, paraphrase using the unrelated word, translation using loan word, cultural substitution, translation by omission, and translation by illustration. In conclusion, the researcher mostly used translation strategy named translation by a more general word in this research which has been determined by analyzing each source of data.